Expression of CD24, a Stem Cell Marker, in Pancreatic and Small Intestinal Neuroendocrine Tumors. Issue 4 (1st October 2015) - Salaria, Safia; Means, Anna; Revetta, Frank; Idrees, Kamran; Liu, Eric; Shi, Chanjuan
Abstract: Objectives: CD24 has been considered a normal and cancer stem cell marker. Potential intestinal stem cells weakly express CD24. In the pancreas, CD24 is a possible cancer stem cell marker for ductal adenocarcinoma. Methods: Expression of CD24 in intestinal and pancreatic neuroendocrine tumors (NETs) was examined. Immunohistochemistry was performed on benign duodenum, ileum mucosa, and pancreas, as well as primary duodenal, primary and metastatic ileal, and pancreatic NETs. Results: Scattered CD24-positive cells were noted in the duodenal and ileal crypts, most of which showed a strong subnuclear labeling pattern. Similar expression was observed in 41 (95%) of 43 primary ileal NETs but in only four (15%) of 26 duodenal NETs ( P < .01). In addition, metastatic ileal NETs retained CD24 expression. Pancreatic islets did not express CD24, and only rare cells had subnuclear labeling of CD24 in the pancreatic ducts. Unlike ileal NETs, only five (5%) of 92 pancreatic NETs expressed CD24 in the subnuclear compartment ( P < .01). All five NETs showed a unique morphology with prominent stromal fibrosis. Conclusions: CD24 expression was frequent in primary and metastatic midgut NETs but rare in pancreatic and duodenal NETs. Expression of CD24 in ileal NETs may have future diagnostic and therapeutic implications.